Peningkatan Kesadaran Bahaya Merokok Melalui Penyuluhan Kesehatan di RT 09 Kelurahan Jembatan Kecil Kota Bengkulu - Delta Aprianti; Dilfera Hermiati; Fitriana Fitriana; Elda Destika Elda Destika; Ricky Casanopa; Tika Septiana Widodo (Utami Publisher, 2026)
Smoking is one of the major public health problems that can cause various chronic diseases and reduce quality of life. This community service activity aimed to increase public awareness and knowledge about the dangers of smoking through health education in RT 09, Jembatan Kecil Village, Singaran Pati District, Bengkulu City. The method used was health counseling with lectures, discussions, and leaflet distribution, preceded by early detection of non-communicable diseases. The participants were residents of RT 09, especially adult males with smoking habits. The results showed an increase in participants’ knowledge regarding the definition of smoking, harmful substances in cigarettes, health risks, and strategies to quit smoking. This activity indicates that health education is effective in improving community awareness of smoking hazards. Continuous and routine health promotion activities are recommended to support healthy behavior change in the community